Eﬀectiveness of Brandt-Daroﬀ exercises in benign paroxysmal positional vertigo: a systematic review - Bagri, Meenakshi; Joshi, Shabnam; Rani, Vandana; Chaturvedi, Rekha; Sabharwal, Jyoti (Wydawnictwo Akademii Wychowania Fizycznego im. Polskich Olimpijczyków we Wrocławiu, 2024)
Introduction. Benign Paroxysmal Positional Vertigo (BPPV) is deﬁned as a disorder of the inner ear characterised by repeated episodes of positional vertigo. BPPV is one of the most prevalent vestibular disorders in the general population, accounting for one-third of all vestibular disorders. The prevalence of BPPV is higher in females than males and this prevalence increases with increasing age. The common non-surgical treatments of BPPV are repositioning manoeuvres and habituation exercises. This review aimed to explore the eﬀectiveness of Brandt-Daroﬀ exercises in patients with BPPV.Methods. Two search engines, PubMed and Cochrane, were used. Articles focusing on Brandt-Daroﬀ exercises as management of BPPV were included in this review. All articles were published in English and results up to February 2023 were included.Results. Epley’s repositioning manoeuvre is a better treatment option for posterior canal BPPV. Epley’s manoeuvre is more eﬀective if applied alone as compared to its application along with Brandt-Daroﬀ exercises or with medication. Epley’s manoeu-vre was more eﬀective than any other repositioning manoeuvre, such as the Semontmanoeuvre. The application of Brandt-Daroﬀ was ineﬀective when applied alone. However, it was eﬀective when applied in combination with the Cawthorne-Cooksey exer-cises in reducing the symptoms of BPPV.Conclusions. Brandt-Daroﬀ exercises have inconsistent results in the treatment of BPPV; hence, high-quality randomised con-trolled trials should be carried out to investigate their eﬃcacy.
Keywords: benign paroxysmal positional vertigo; vestibular diseases; habituation; rehabilitation